2022
DOI: 10.1007/s40273-022-01130-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Digital Health Interventions: Methodological Issues and Recommendations for Practice

Abstract: Health care interventions are increasingly being delivered through digital technologies, offering major opportunities for delivering more health gains from scarce health care resources. Digital health interventions (DHIs) raise distinct challenges for economic evaluations compared with drugs and medical devices, not least due to their interacting, evolving features. The implications of the distinctive nature of DHIs for the methodological choices underpinning their economic evaluation is not well understood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 41 publications
3
67
0
Order By: Relevance
“…These analyses should consider the end-user perspective as well as the potential benefits for the health care system in general [ 168 , 169 ]. Digital health interventions appear to be cost-effective [ 170 ], although reports often present varying, inconclusive results [ 171 ]. Although it is often mentioned that one of the potential advantages of digital health interventions, particularly in the long term, may be a significant decrease in health care costs [ 172 ], the upfront expenses of developing the digital intervention might be substantial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses should consider the end-user perspective as well as the potential benefits for the health care system in general [ 168 , 169 ]. Digital health interventions appear to be cost-effective [ 170 ], although reports often present varying, inconclusive results [ 171 ]. Although it is often mentioned that one of the potential advantages of digital health interventions, particularly in the long term, may be a significant decrease in health care costs [ 172 ], the upfront expenses of developing the digital intervention might be substantial.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increasing importance of conducting economic evaluations of digital health care interventions, only 2% (1/55) of the studies included in our reviews reported economic evaluation data [ 73 ]. Recent documents from the World Health Organization [ 168 ] and the International Training and Education Center for Health [ 169 ] at the University of Washington in the United States, as well as a recent review [ 171 ], present a practical overview of how to perform economic evaluations.…”
Section: Resultsmentioning
confidence: 99%
“…Once an application is developed and operational in a market, the marginal cost of treating an additional patient is quite low and thus more scalable. However, insurance coverage for app-based therapy is still very limited [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…DHI development incurs significant research and development costs prior to launch, and the resources consumed during development can be very different from pharmaceuticals and physical medical devices. DHIs have other unique characteristics that can affect development processes and thus costs, including faster evolution, active and more dynamic user input ( 21 ). DHI development costs are usually incurred for content and software design, website and graphic design, digital platform development and regulatory approval processes.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to describe, estimate, and present the associated cost components and total cost of developing and delivering the Narrative Experiences Online (NEON) Intervention, using current recommendations for costing DHIs ( 11 , 19 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%